2023
DOI: 10.1001/jamaophthalmol.2023.2672
|View full text |Cite
|
Sign up to set email alerts
|

Some Lessons Regarding Intraocular Lens Implantation Following Pediatric Cataract Surgery

Abstract: data are immediately useful to children (and their parents or guardians) who are considering cataract surgery, as well as to the pediatric ophthalmologists who are monitoring these children for complications after cataract surgery. Hopefully, PEDIG will continue their research efforts in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…After cataract extraction with primary IOL implantation in children, visual axis opacification is the most common complication requiring reoperation [ 16 , 17 , 19 ]. In a 5-year follow-up study after cataract surgery among children younger than 13 years, the cumulative incidence of significant visual axis opacification was reported as 33% for bilateral pseudophakia and 34% for unilateral pseudophakia [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After cataract extraction with primary IOL implantation in children, visual axis opacification is the most common complication requiring reoperation [ 16 , 17 , 19 ]. In a 5-year follow-up study after cataract surgery among children younger than 13 years, the cumulative incidence of significant visual axis opacification was reported as 33% for bilateral pseudophakia and 34% for unilateral pseudophakia [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior long-term studies indicated a frequent occurrence of glaucoma-related complications following infantile cataract removal [3,7]. On the other hand, more recent reports utilizing modern surgical techniques revealed a reduced incidence of glaucoma in pseudophakic eyes, indicating that primary IOL implantation combined with anterior vitrectomy does not elevate the risk of secondary glaucoma [16][17][18][19]. In addition, other large-scale analyses underscored that primary IOL implantation serves as a protective factor against glaucoma development after congenital cataract surgery [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%